In vitro Regeneration and Flower Induction on Solanum nigrum L. from Pachamalai hills of Eastern Ghats (Plant Tissue Culture and Biotechnology, 2009)
Explants of Solanum nigrum L., collected from Pachamalai hills callused successfully on MS basal medium supplemented with IAA and BAP. The highest frequency of green compact callus and multiple shoots were obtained on MS containing 2.0 mg/l IAA and 0.5 mg/l BAP. The callus when cultured on MS basal medium fortified with different concentrations of BAP (3.0 - 8.0 mg/l) and IAA (0.5 mg/l) showed multiple shoot formation. The highest frequency of multiple shoots was obtained on MS containing 6.0 mg/l BAP and 0.5 mg/l IAA. For in vitro flowering, the node explants were cultured on MS fortified with different concentrations of BAP (2.0 - 7.0 mg/l) and NAA (0.5 mg/l). The highest number of multiple shoots were obtained in MS supplemented with 6.0 mg/l BAP and 0.5 mg/l NAA. The in vitro flowering was observed on MS containing 2,4-D and BAP 1.5 mg/l, respectively. The best rooting was obtained on MS containing 0.5 mg/l IBA. The well-rooted plants were hardened and finally planted in the garden.  Key words: In vitro studies, Medicinal plant, Solanum nigrum, Node, Callus D.O.I. 10.3329/ptcb.v18i1.3264 Plant Tissue Cult. & Biotech. 18(1): 43-48, 2008 (June)